Two visions of a paper - Belanger, Simon (My University, 2023)
Two Visions of a Paper guides students on how to write correctly for academic purposes based on principles and ideas from Plato's Gorgias and Meno. The paper contrasts the dialectical with the rhetorical methods of speech that appear throughout Plato's works and relates these methods to the paper writing process to illustrate which mode the student should pursue. The paper plays with ideas such as Socratic irony, when persuasive verbiage is essential, the movement between part and the whole and other ideas from Plato.
Presented on April 19, 2024 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: paper writing; writing skills; post-secondary education